A surprising treatment response in a patient with rare isolated growth hormone deficiency, type IB. (9th November 2017) - Amar, Jordan Yardain; Borden, Kimberly; Watson, Elizabeth; Arslanian, Talin
Summary: Isolated Growth Hormone Deficiency (IGHD) is a rare cause of short stature, treated with the standard regimen of subcutaneous synthetic growth hormone (GH). Patients typically achieve a maximum height velocity in the first year of treatment, which then tapers shortly after treatment is stopped. We report a case of a 9-year-old male who presented with short stature (<3rd percentile for age and race). Basal hormone levels showed undetectable serum IGF1. Skeletal wrist age was consistent with chronologic age. Cranial MRI revealed no masses or lesions. Provocative arginine-GH stimulation testing demonstrated a peak GH level of 1.4 ng/mL. Confirmatory genetic testing revealed a rare autosomal recessive single-nucleotide polymorphism (SNP) with mutational frequency of 2%. GH supplementation was started and pursued for 2 years, producing dramatically increased height velocity. This velocity persisted linearly through adolescence, several years after treatment had been discontinued. Final adult height was >95th percentile for age and race. In conclusion, this is a case of primary hypopituitarism with differential diagnosis of IGHD vs Idiopathic Short Stature vs Constitutional Growth Delay. This case supports two objectives: Firstly, it highlights the importance of confirmatory genetic testing in patients with suspected, though diagnostically uncertain, IGHD. Secondly, it demonstrates a novel secondary growth pattern with implications for better understanding the tremendous variability of GH treatment response. Learning points: GHD is a common cause of growth retardation, and IGHD is a specific subtype of GHD in which patients present solely with short stature. The standard treatment for IGHD is subcutaneous synthetic GH until mid-parental height is reached, with peak height velocity attained in the 1st year of treatment in the vast majority of patients. Genetic testing should be strongly considered in cases of diagnostic uncertainty prior to initiating treatment. Future investigations of GH treatment response that stratify by gene and specific mutation will help guide treatment decisions. Response to treatment in patients with IGHD is variable, with some patients demonstrating little to no response, while others are 'super-responders.'